1974
DOI: 10.1515/hfsg.1974.28.2.41
|View full text |Cite
|
Sign up to set email alerts
|

Feeding and Survival Responses ofReticulitermes flavipes(Kollar) to Extractives of Wood from 11 Coniferous Genera

Abstract: Keywords Coniferous wood Protozoa Termite resistance Wood extractives Reticulitenmes flavipes Schlüsselwörter (Sachgebiete) Nadelhölz-er Protozoen TerfFiiteflf-'esistenz Holzini lalttsstoffc s flavipes Feeding and Survival Responses of Reticulitermes flavipes (Kollar) to Extractives of Wood from u Coniferous GeneraSummary Woods unfavorable to Reticulitermes flavipes (Kollar) in a force-feeding test on heartwood blocks of 11 American coniferous genera included Port-Orford-cedar, eastern redcedar, western redced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 3 publications
0
23
0
Order By: Relevance
“…The oil content of cedar apparently increases the wood's resistance to decay and termites (Carter and Smythe 1974) and is said to have insecticidal properties (Schenck 1912). The heartwood contains fewer compounds than do other Cupressaceae (Erdtman and Norin 1966), although it seems to have been less completely studied.…”
Section: Root Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The oil content of cedar apparently increases the wood's resistance to decay and termites (Carter and Smythe 1974) and is said to have insecticidal properties (Schenck 1912). The heartwood contains fewer compounds than do other Cupressaceae (Erdtman and Norin 1966), although it seems to have been less completely studied.…”
Section: Root Systemmentioning
confidence: 99%
“…Port-Orford-cedar heartwood was more toxic to termites (Reticulitermes flavipes [Kollar]) than were 10 other woods, apparently because of its oil content (Carter and Smythe 1974). Termites will, however, attack weathered Port-Orford-cedar wood from which the oil presumably has been lost.…”
Section: Resistance T O I N D E N T a T I O N Onmentioning
confidence: 99%
“…Factors affecting wood consumption by termites are numerous and complexly related (Peralta et al, 2004). Most important factors are wood species, hardness, presence of toxic substances, feeding inhibitors or deterrents, presence or absence of fungi, degree of fungal decay, moisture content of wood and soil (Carter & Smythe, 1974;Nagnan and Clement, 1990). Qureshi et al (2012) found in their study that the death of the termites is due to the mortality of their protozoan population during the period of experimentation which appears to be due to the toxic effect of corresponding wood and not because of non-feeding of the woods.…”
mentioning
confidence: 99%
“…The natural resistance of wood to termite attack is caused in part by chemicals deposited in wood during heartwood formation (Kumar 1971, Beal et al 1974, Carter and Smythe 1974, McDaniel 1989. The activities of these chemicals usually differ among trees within a species and may vary among locations in individual trees.…”
mentioning
confidence: 99%
“…The activities of these chemicals usually differ among trees within a species and may vary among locations in individual trees. Different wood contains different insecticidal chemicals and can be expected to vary in its resistance to wood-destroying insects (Carter andSmythe 1974, Carter andMauldin 1981). Also, the extractive components in termite-resistant wood may be contact toxin to termites or act as antifeedants, repellents, or protozoacides (Saeki et al 1971, Saeki 1973, Carter 1979, French et al 1979, Carter and Mauldin 1981.…”
mentioning
confidence: 99%